2003
DOI: 10.1083/jcb.200304154
|View full text |Cite|
|
Sign up to set email alerts
|

Integrin-linked kinase is required for laminin-2–induced oligodendrocyte cell spreading and CNS myelination

Abstract: Early steps in myelination in the central nervous system (CNS) include a specialized and extreme form of cell spreading in which oligodendrocytes extend large lamellae that spiral around axons to form myelin. Recent studies have demonstrated that laminin-2 (LN-2; α2β1γ1) stimulates oligodendrocytes to extend elaborate membrane sheets in vitro (cell spreading), mediated by integrin α6β1. Although a congenital LN-2 deficiency in humans is associated with CNS white matter changes, LN-2–deficient (dy/dy) mice have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
145
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(155 citation statements)
references
References 43 publications
8
145
2
Order By: Relevance
“…Our studies in vitro, in cultured oligodendrocyte progenitors, indicate that stathmin is elevated by stimuli favoring migrations (i.e., PDGF and bFGF) (Fig. 1), and its expression is downregulated by differentiative stimuli, such as mitogen withdrawal and growth on a laminin substrate, known to favor membrane spreading and myelin formation (Buttery and ffrench-Constant, 1999;Chun et al, 2003). In vivo, in physiological conditions, stathmin is expressed by migratory precursors labeled by PSA-NCAM (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies in vitro, in cultured oligodendrocyte progenitors, indicate that stathmin is elevated by stimuli favoring migrations (i.e., PDGF and bFGF) (Fig. 1), and its expression is downregulated by differentiative stimuli, such as mitogen withdrawal and growth on a laminin substrate, known to favor membrane spreading and myelin formation (Buttery and ffrench-Constant, 1999;Chun et al, 2003). In vivo, in physiological conditions, stathmin is expressed by migratory precursors labeled by PSA-NCAM (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Normal myelination in the optic nerve, corpus callosum, and spinal cord in the absence of ␤1-integrin Previous studies on ECM function in myelination revealed important regional differences in the requirement for these molecules (Chun et al, 2003). Therefore, we analyzed myelination in the optic nerve, corpus callosum, and spinal cord.…”
Section: Targeted Deletion Of the ␤1-integrin Gene Results In Proteinmentioning
confidence: 99%
“…In support of such a role, oligodendrocytes cultured on laminin-2, an ECM molecule expressed in the developing mammalian CNS Tian et al, 1997;Powell et al, 1998), produce enhanced myelin membranes , whereas mice and humans lacking the laminin ␣2 chain (present in laminin-2) show dysmyelination (Jones et al, 2001;Chun et al, 2003). Antibody-blocking experiments and expression of a ␤1-integrin dominant-negative chimeric integrin, ␤1-DN (Relvas et al, 2001), showed that the oligodendrocyte integrin mediating this process is probably ␣6␤1-integrin, the putative laminin integrin receptor expressed by oligodendrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that extracellular matrix components, such as laminin-2, promote extensive membrane extension in oligodendrocytes through integrin interactions (Buttery and ffrenchConstant, 1999;Chun et al, 2003;Colognato et al, 2004). The specific downregulation of a clathrin-independent endocytosis pathway by attachment to the extracellular matrix is interesting in this aspect (del Pozo et al, 2005).…”
Section: Discussionmentioning
confidence: 99%